Assessment of point-of-care testing for prediction of aromatase inhibitor-associated side effects in obese postmenopausal breast cancer patients screened for cardiovascular risk factors - Milambo, Jean Paul Muambangu (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.